TyG-WC Index as a Superior Predictor of Hyperuricemia Risk in the Hypertensive Population: A Prospective Cohort Study - Zhang Q; Liu J; Zhang R; Wang C; Song Y; Wang X; Zeng F (Diabetes, Metabolic Syndrome and Obesity)
Qin Zhang,1,* Jian Liu,2,* Ruize Zhang,3 Changfen Wang,4 Yanyan Song,5 Xi Wang,2 Fanling Zeng6 1Department of Cardiology, Xi Chang People’s Hospital, Xi Chang, Sichuan Province, 615000, People’s Republic of China; 2Department of Cardiology, The First Affiliated Hospital of Chongqing Medical University, Chongqing, 400016, People’s Republic of China; 3Dougherty Valley High School, San Ramon, CA, 94582, USA; 4Department of Cardiology, People’s Hospital of Qianxinan Prefecture, Guizhou Province, People’s Republic of China; 5Department of Endocrinology, Chongqing Jianshe Hospital, Chongqing, People’s Republic of China; 6Health Management Ctr, The First Affiliated Hospital of Chongqing Medical University, Chongqing, 400016, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xi Wang; Fanling Zeng, The First Affiliated Hospital of Chongqing Medical University, No. 1 Youyi Road, Yuzhong District, Chongqing, 400016, People’s Republic of China, Email 201884@cqmu.edu.cn; zengfanling@hospital.cqmu.edu.cnObjective: To evaluate the predictive value of the triglyceride-glucose waist circumference index (TyG-WC) for hyperuricemia (HUA) risk in the hypertensive population.Methods: This prospective cohort study involved 831 hypertensive patients with normal uric acid levels, who underwent continuous health examinations for five years. Participants were categorized into four groups based on baseline TyG-WC quartiles, and the incidence of hyperuricemia was monitored in each group. Hazard ratios (HRs) and 95% confidence intervals (95% CIs) for HUA incidence were calculated using Cox proportional hazards regression analysis. The predictive ability of various TyG indices for HUA was evaluated using receiver operating characteristic curves.Results: After five years of follow-up, 117 participants developed HUA. The cumulative incidence of HUA was significantly higher in the highest TyG-WC quartile (Q4) compared to the lowest quartile (Q1). The TyG-WC index demonstrated the highest predictive value, with an area under the curve of 0.685 (95% CI: 0.635– 0.734) compared to other obesity-related TyG indices. After adjusting for confounding factors, per standard deviation increase in the TyG-WC index was associated with a 1.28-fold higher risk of developing HUA (95% CI: 1.04– 1.56, P < 0.001).Conclusion: The TyG-WC index is a robust independent predictor of HUA risk in the hypertensive population. It provides a practical, reliable, and cost-effective tool for the early identification of high-risk individuals in this population.Keywords: hypertension, hyperuricemia, TyG-WC index, insulin resistance, obesity